Heterogeneous multi-core systems for bioinformatics - Adrianto Wirawan (2010)
The bioinformatics research area is now faced with an obstacle of ever-increasing biological data to verify their biological discovery. As data increases, so does the workload for managing, processing and analysing this data. Combined with the inherent complexity of biological problems, traditional approaches results in long run-time and huge memory requirements. The emergence of accelerator technologies such as multi-core architectures provides the opportunity to achieve significant improvements in execution time for many bioinformatics applications, compared to sequential general-purpose platforms. Using multi-cores to solve large scale bioinformatics applications, such as sequence analysis, is therefore a promising and challenging research field, since large-scale computational bioinformatics problems can benefit much from this kind of processing power.